Fellow Designations of Interest to Nurse Leaders. (January 2022) - Herrin-Griffith, Donna; Waxman, KT
Abstract : Achieving fellow designation is commonly a career goal for nurse leaders. The path to achievement can be confusing, and once a goal is set, choosing the right designation is important. This column outlines the background of fellow designation, clarifies differences between fellow designation and other career advancement options, and presents ideas for consideration by nurse leaders as they pursue career advancement through fellow designation.